Performance analysis of melting phenomena in an ice-freezing type direct-contact heat exchanger. (June 2022) - Patel, Parth; Sharma, Amrita; Monde, Aniket D.; Sharma, Manvendra; Mondal, Bobin; Kothadia, Hardik B.
Abstract: The present study endeavours to represent a latest concept of utilizing similar heat transfer fluid (HTF) and phase change material (PCM) in a direct contact type PCM heat exchanger (DCHEX). This technique has been found more effective during melting process. In the following investigation, a segment of the heat exchanger is numerically modelled to analyse the temporal behaviour of the latent heat energy storage system during the cycle of discharging. The transient numerical computation incorporates an iterative, finite volume method based on enthalpy-porosity technique for numerically model the phase change phenomena. For the analysis, water is used as working fluid. To show the performance enhancement of this technique during melting process, a series of simulations are performed to examine the impact of varying HTF inlet condition and flow rates. The changes in the configuration of the heat exchanger are studied. Heat exchanger parameters such as difference between inlet and outlet temperature ( ΔT ), heat release rate ( Q ), temperature effectiveness ( θ ) and volumetric heat transfer coefficient ( U v ) are evaluated for all such cases. A uniform exit temperature of the HTF is observed for most of the time with significant increase in the heat transfer in the direct contact type heat exchanger. Three distinct stages namely initial, intermediate and final phases are observed during the melting process. During the initial phase the parameters exhibits uniform behaviour. In the intermediate phase there is significant drop and rise in the parameters while during the final phase the value of parameters diminishes except for U v . Increasing HTF flow rate promotes increment in heat transfer rate while increasing the inlet temperature of HTF is more desirable to increase the overall heat transfer coefficient. Graphical abstract: Unlabelled Image Highlights: Direct-contact type heat exchanger with identical HTF and PCM material. Effect of operational and geometrical parameter on the heat transfer performance. Thermal performance behaviour: effectiveness, heat release rate and volumetric HTC. Effect of configuration of heat exchanger on the thermal performance of LHTES. Effect of inlet temperature and flow rate of HTF on LHTES.